Christmas tree worm Spirobranchus spp. (Annelida: Serpulidae) as indicators of coral health at Weh Island, Aceh Province, Indonesia - AFKAR AFKAR; TERNALA ALEXANDER BARUS; ARLEN HANEL JOHN; MUHAMMAD ALI SARONG (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Afkar, Barus TA, John AH, Sarong MA. 2024. Christmas tree worm Spirobranchus spp. (Annelida: Serpulidae) as indicators of coral health at Weh Island, Aceh Province, Indonesia. Biodiversitas 25: 1743-1753. The research was conducted along 300-m long transects at 3 and 7 m depth in Beurawang Waters, Weh Island, Aceh Province, Indonesia, which aimed to analyze the association of christmas tree worms (Polychaeta: Serpulidae: Spirobranchus) with coral health conditions and determine the impact of their presence on the coral reef ecosystem. On average, Spirobranchus individuals were more commonly found at 3 m than at 7 m depth. Spirobranchus was found to be most associated with massive corals of the genus Porites. Spirobranchus tends to be most abundant in damaged coral reef colonies, which suggests that coral conditions could worsen if the abundance of Spirobranchus worms increases. Statistical analysis also shows an association between the abundance of Spirobranchus and the condition of coral reefs, with a 'strong' relationship value of 0.611. Therefore, it is necessary to consider coral transplantation as an effort to repair damaged coral substrates in Beurawang Waters.